Apostolate of the laity: a re-discovery of holistic post-war missiology in Scotland, with reference to the ministry of Tom Allan - Forsyth, Alexander Craig (The University of Edinburgh, 2014)
This thesis offers principles for Christian mission in the present Western milieu derived from a retrieval of the missiology in post-war Scotland of Tom Allan. Allan was a minister, evangelist and theologian of particular public prominence in Scotland and beyond in the period from 1946 to 1964. His missiology focused upon the ‘apostolate of the laity’ through the ‘contextualisation’ of Christianity and Church. It was drawn from diverse, rich sources in Scottish and European theology and tradition. Allan’s gift was to collate and apply such influences contextually to two working-class parishes in Glasgow, and to articulate them within his seminal work on lay evangelism, The Face of My Parish. From 1953 to 1955, Allan was the Field Director of the ‘Tell Scotland’ Movement, which sought to implement his missiology on a national scale. The decision, at Allan’s instigation, to invite Billy Graham to conduct the ‘All-Scotland Crusade’ of 1955 diverted attention from Allan’s lay missiological focus, fatally polarised the differences in emphasis within the Movement, and has since tainted the perception of mission in Scotland. Following consideration of the implementation of Allan’s model of mission, analysis is undertaken of his sources and inspirations, of the underlying causes of the triumphs and failures of his model, and of Allan’s place in mission theology. In particular, inherent tensions are considered between aspects of the model which together straddle the ‘modern’ and ‘postmodern’ to form a ‘tale of two paradigms’; such as the reliance on the institutional Church as both agent and object of mission or the utilisation of mass evangelism, in contrast with the overarching purpose of the lay formation of a New Testament koinonia by a ‘congregational group’. Consideration of Allan’s work is thereafter broadened by considering several contemporaneous streams which further enhanced ‘contextualisation’ of both mission and Church, to be exercised by and for ordinary people: the East Harlem Protestant Parish; the Gorbals Group Ministry; and Robert Mackie, Ian Fraser and Scottish Churches House. Then viewing the work of Allan and his contemporaries through the lens of present global missiology and sociological theory, general principles are derived for mission now. Such principles form the basis of a model within ‘late modernity’ of contextual mission which might move beyond the private/public constraint on religious expression. It is a model of ‘local’ mission in conversation with the ‘global’, by the empowerment of the laity to act within the ‘micro-cultures’ which they inhabit. It is a model which re-asserts the primacy of the ‘whole people of God’; seeking the organic growth of koinonia with or without reference to the institutional Church; through a ‘both/and’ missiology of word and deed; exercising ‘prophetic dialogue’ in ‘bold humility’; in cross-cultural translation as a two-way process towards a fuller ‘interculturation’.
Keywords: theology; mission; laity; Allan, Tom